PERAN KETERLIBATAN PRODUK DALAM MEMODERASI HUBUNGAN ANTARA KUALITAS LAYANAN DARING TERHADAP KEPUASAN DARING - Jannah, Miftahul; Nugroho, Sahid Susilo; Gitosudarmo, Indriyo (Buletin Studi Ekonomi; VOL.24.NO.2.AGUSTUS 2019DO - 10.24843/BSE.2019.v24.i02.p10, 2019)
Abstract: The Role of Product Involvement in Moderating the Relationship Between Online Service Quality and Online Satisfaction. The moderating effect of product involvement on the relationship between e-service quality and e-satisfaction. This study is aimed to examine the effect of five dimensions of e-service quality: (1) website design, (2) reliability, (3) customer service, (4) security/privacy, and (5) after sales service, on e-satisfaction and e-loyalty. The study also analyzed the moderating effects of product involvement on the relationship between e-service quality and e-satisfaction. A quantitative study approach using survey method is adopted to reach 228 respondents. The data is analyzed by simple, multiple , and hierarchical regression methods to explore direct and moderating effect among intended variables. The study findings confirmed that reliability, customer service, and after sales service have influenced e-satisfaction. Keywords: e-service quality; e-satisfaction; product involvement.